Calculation of Steel Pipeline Corrosion Depth at the Galvanic Corrosive Element Operation - Stepova, Olena; Parashchiienko, Iryna; Lartseva, Iryna (International Journal of Engineering and Technology, 2018)
The work is devoted to the issue of calculating the safe life of steel pipelines, which is in accordance with the definition of the residual thickness of the pipe wall.The purpose of this work is to develop a dependence, permitting to calculate the corrosion depth of the steel pipeline in the crack of the insulation coating under the action of an electrolytic medium aggressive to the pipeline metal. To achieve this goal, the following tasks were solved: to develop a dependence based on the mathematical model of a local corrosion element, that would allow to calculate the steel pipeline corrosion depth in the crack of the insulating coating, which would be based on real parameters obtained during the structures examination; to conduct an experimental verification of the steel pipeline’s corrosion damage depth during the galvanic corrosion element’s operation.Based on the mathematical model of the pipeline’s electrochemical corrosion in the crack of the insulating coating under the action of an the electrolytic medium aggressive to the pipeline metal, a dependence was obtained permitting to calculate the depth of the pipeline’s wall corrosion during the work of the macro-galvanic corrosion couples and the stable presence of an aggressive solution in the damaged zone. The experimental studies have proved that direct corrosion tests are consistent with the design values of the macro-galvanic couple’s current. The advantage of this model is the ability to predict the development of corrosion in time, regardless of the aggressive electrolyte’s chemical composition, the possibility of obtaining the required calculation parameters using the structures operated.